Cocoa production systems vs environmental resources. A current strategic challenge - Mendoza Vargas, Emma Yolanda (2021)
Although the use of sustainable practices has become widespread in recent years, a range of adverse environmental and social effects persist that threaten to reverse the productive and economic development achieved. This research aims to carry out an analysis regarding the environmental challenges of sustainable cocoa production systems. From the documentary review and the investigation of the literature, it was possible to determine that, at the global level, cocoa production requires the rational use of environmental resources, since pollution and wastes grow. In addition, the demand for its derivatives has focused on the consumption of a more environmentally friendly offer. Therefore, it has been emphasized in the literature and from multilateral organizations that creating more efficient production systems is an urgent need. Given these recommendations, the purpose of this study is to offer a reflective and panoramic view on cocoa production systems and their impact on environmental resources, their implication, consequences, risks, and the challenge that represents a change in this dynamic. The importance of implementing a productive management system that stands out for its economic, ecological and social sustainability is a key challenge that is part of the conclusions obtained with the theoretical reflection presented on cocoa production systems and environmental resources.